The Aesthetics of Everyday Life: the Aesthetics of the Encounter - Korusiewicz, Maria (Studia Ecologiae et Bioethicae, 2016)
Everyday aesthetics is the umbrella term for trends in contemporary aesthetics which focus on everyday existence. Its specifics require changes and innovations in traditional aesthetic theories. Everyday aesthetics can be related to the so-called engaged aesthetics of Arnold Berleant: it takes into consideration such aspects of aesthetic experience as its emotional character, sensuality, directness, and its open “boundaries.” Everyday aesthetics covers the whole spectrum of the forms of aesthetic appreciation from disinterested contemplation to active participation founded on cooperation with the environment and the notion of aesthetic welfare.” Introducing the categories of respect, care and attentiveness toward objects, processes, and other – human and non-human – beings, everyday aesthetics can be viewed as the “aesthetics of encounter.” The text attempts to present and discuss its main premises.